Nestin overexpression in hepatocellular carcinoma associates with epithelial-mesenchymal transition and chemoresistance - Zhang, Yan (J Exp Clin Cancer Res, 2016)
BACKGROUND: Nestin expression has been reported to be associated with the prognosis of many solid tumors including human hepatocellular carcinoma (HCC). The present study aimed to identify the role, if any, of Nestin in the chemotherapeutic treatment of HCC. METHODS: We determined Nestin expression in nine HCC cell lines and 220 tissue samples of advanced HCC patients (retrospectively registered) treated with FOLFOX regimens. We examined the correlations between Nestin expression and clinicopatholgical variables and HCC prognosis. Also, we used in vitro and in vivo methods to determine the effects of Nestin expression on HCC cell invasion, migration and chemosensitivity. RESULTS: Nestin expression was significantly increased in HCC tissues and drug-resistant cell lines, and the presence of high levels of Nestin was associated with poor survival. We also showed that drug-resistance occurred in HCC cells with epithelial-mesenchymal transition (EMT), which in turn enhanced invasion ability. Nestin depletion reversed drug-resistance in the Bel-7402/5-FU and Bel-7402/ADM cell lines. Nestin knockdown enhanced chemotherapeutic efficacy in nude mice. Moreover, Nestin up-regulation in Bel-7402 was associated with the activation of Wnt/β-catenin signaling. CONCLUSION: Our findings suggest that Nestin inhibitors may be useful for the chemotherapy of HCC. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13046-016-0387-y) contains supplementary material, which is available to authorized users.